NORMAL PLANTAR FASCIA THICKNESS IN ADULT - Siahaan, Yusak Mangara Tua; Gunawan, Pricilla Yani; Haryanto, Jeffry Foraldy; Sungono, Veli (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Background: Plantar fasciitis is a common problem caused by thickening of the plantar fascia. The normal plantar fascia thickness ranged between 2-3 mm and it was generally accepted that value more than 4mm was considered pathologic.Objective: to identify normal plantar fascia thickness in adults using ultrasonography.Methods: This is a cross sectional study measuring the thickness of plantar fascia in 145 subjects with no history of heel pain. Plantar fascia thickness was measured in both feet using an ultrasound. Age, height and weight were recorded and analysed.Results: As much as 145 subjects were included in this study. Male to female ratio was 0.7. Mean age was 44 and body mass index (BMI) was mostly within normal range. Plantar fascia thickness in male was 2.71 ± 0.48 mm in right foot, and 2.74 ± 0.47 mm in left foot. Fascia thickness in female was 2.55 ± 0.50 mm in right foot, and 2.57 ± 0.45 mm in left foot. There was a significant plantar fascia thickness difference between male and female (p = 0.035 in right foot, and p=0.04 in left foot). Age, weight and BMI had a significant correlation towards plantar fascia thickness. In multivariate analysis, age and BMI revealed to have a linear correlation to plantar fascia thicknessConclusion: Age and BMI were found to be the best predictive factor of plantar fascia thickness.